Is the Volume-Based Thermodynamics (VBT) Approach Valid for the Estimation of the Lattice Enthalpy of Salts Containing the 5,5'-(Tetrazolate-1N-oxide) Dianion? - Glasser, Leslie; Jenkins, H.D.; Klapotke, T. (John Wiley & Sons Ltd, 2014)
In previous publications we have used volume-based thermodynamics (VBT) to estimate the lattice energies and enthalpies of new high-energy ionic materials. The use of the VBT approach for salts containing non-spherical ions such as the 5,5′-(tetrazolate-1N-oxide) dianion in TKX-50 [bishydroxylammonium 5,5′-(tetrazolate-1N-oxide)] has received some criticism. Herein we show that the VBT approach is suitable for the estimation of lattice energies/enthalpies for such salts.